PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO ANIMASI TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PEREDARAN DARAH MANUSIA DI KELAS XI SMA NEGERI 1 SINGINGI - Meidelvi, Syahdu; Fitra Suzanti; Resma Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes of students on the topic of the human circulatory system indicate the need for instructional models and learning media that can enhance student engagement and understanding. The human circulatory system is considered an abstract and complex topic, requiring learning approaches that foster problem-solving skills and are supported by effective visual media. This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by animated video media on students’ learning outcomes regarding the human circulatory system in Grade XI of SMA Negeri 1 Singingi. This research employed a quasi-experimental method using a pretest-posttest non-equivalent control group design. The sample consisted of two classes: an experimental class that received instruction through the PBL model assisted by animated videos and a control class that was taught using the Discovery Learning model. Data were collected through pretests and posttests and analyzed using descriptive and inferential statistics. The results showed that the mean posttest score of the experimental class was 83.89, which was higher than that of the control class at 55.14. The N-Gain score of the experimental class was 0.62 (moderate category), while the control class achieved an N-Gain score of 0.28 (low category). Furthermore, the Mann–Whitney test yielded a significance value of 0.000 (p < 0.05), indicating that the Problem Based Learning model assisted by animated videos had a significant effect on students’ learning outcomes regarding the human circulatory system in Grade XI of SMA Negeri 1 Singingi. Therefore, the implementation of the PBL model assisted by animated video media was effective in improving students’ learning outcomes.